Creating Musculoskeletal Programs for Culturally Diverse, Underserved Communities: A Community-Based Participatory Research Survey. Issue 3 (October 2014) - Goldsmith, Sandra; Friedman, Dana; Horton, Roberta; Seehaus, Mavis; Robbins, Laura
Background: Arthritis and other musculoskeletal diseases are the most prevalent health conditions in the USA, causing enormous financial and social burdens, especially in underserved communities. Targeted care and prevention programs are urgently needed. Questions/Purposes: Within an overall goal of revealing health disparities, the questionnaire explored (1) the use of and access to healthcare, (2) the factors affecting quality of life, and (3) the levels of provider–patient communication. Methods: A New York City musculoskeletal hospital conducted a community health needs survey among its diverse ethnic/racial communities. A 39-item questionnaire was administered online, by mail, and in person (in English, Spanish, and Chinese). Answers were analyzed in terms of sociodemographics, to define health disparities within a total sample and two subsamples. Results: In the total sample, respondents were 60% White, 16% Black, 14% Hispanic/Latino, and 11% Asian, mostly female, and aged 50 to 79. More than 17% of the total sample indicated they could not access a healthcare provider when needed. Poor nutrition and lack of physical activity were large areas of concern, as were falls and poor self-reported health status. Nearly all respondents said they took steps to communicate with their healthcare providers. Dramatic health disparities were found between Whites and non-Whites (e.g., non-Whites were most likely to rate their health poorly, consider their diet fair or poor, lack health insurance, and be unable to access a healthcare provider). Conclusion: The findings are being used to further refine, develop, and expand the hospital's community programs, especially for culturally diverse and underserved communities.